Efficient revocable attribute-based encryption scheme - Xuejun LI; Dan ZHANG; Hui LI (Tongxin xuebao)
In the existing solutions,the time-based scheme is difficult to achieve immediate revocation,and the third-party-based scheme often requires re-encryption,which needs large amount of calculation and doesn’t apply to mas-sive data.To solve the problem,an efficient and immediate CP-ABE scheme was proposed to support user and attribute lev-els revocation.The scheme was based on the classic LSSS access structure,introducing RSA key management mechanism and attribute authentication.By means of a semi-trusted third party,the user could be authenticated before decryption.Com-pared with the existing revocation schemes,The proposed scheme didn’t need the user to update the key or re-encrypt the ciphertext.The semi-trusted third party wasn’t required to update the RSA attribute authentication key.The scheme greatly reduced the amount of computation and traffic caused by revocation,while ensuring anti-collusion attacks and forward and backward security.Finally,the security analysis and experimental simulation show that the scheme has higher revocation ef-ficiency.